2013
DOI: 10.1007/s12640-013-9393-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytokine and BDNF Levels in Autism Spectrum Disorder

Abstract: The contribution of neuroimmune functioning and brain-derived neurotrophic factor (BDNF) to functional dysregulation in autism spectrum disorder was assessed in 29 patients under treatment in two specialized centers of Basilicata (Chiaromonte and Matera), Southern Italy, through analysis of serum levels of cytokines and BDNF. Elevated levels of the pro-inflammatory cytokine, including interleukin-1, interleukin-6, interleukin-12, interleukin-23, tumor necrosis factor-α and BDNF were observed, regardless of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 53 publications
8
91
1
Order By: Relevance
“…Previous studies revealed activation of the Th1 system with increased production of IL-12 and interferon when compared to controls (Stubbs 1995, Singh 1996, and was recently confirmed (Ross et al 2013). Alterations in the level of pro-inflammatory cytokines such as IL-12, IL-1, IL-6, TNF-α, IL-23 and the brain-derived neurotrophic factor (BDNF) in ASD was recently reported (Ricci et al 2013). ASD children express increased IFNγ and IL-1 receptor antagonist (IL-1ra), resulting in a Th1 skewing (Croonenberghs et al 2002a, Goines et al 2011).…”
Section: ↓↑mentioning
confidence: 72%
“…Previous studies revealed activation of the Th1 system with increased production of IL-12 and interferon when compared to controls (Stubbs 1995, Singh 1996, and was recently confirmed (Ross et al 2013). Alterations in the level of pro-inflammatory cytokines such as IL-12, IL-1, IL-6, TNF-α, IL-23 and the brain-derived neurotrophic factor (BDNF) in ASD was recently reported (Ricci et al 2013). ASD children express increased IFNγ and IL-1 receptor antagonist (IL-1ra), resulting in a Th1 skewing (Croonenberghs et al 2002a, Goines et al 2011).…”
Section: ↓↑mentioning
confidence: 72%
“…Increased levels of IL-1β were found in plasma [114,115], serum [116,117], and peripheral blood mononuclear cells (PBMC) [118][119][120]; decreased levels were described in neonatal dried-blood samples (n-DBSS) [121]. In the VPA animal model, IL-1β was increased in the hippocampus [122,123], an LPSexposed hippocampus [109], and a whole-brain homogenate [124].…”
Section: Interleukin 1βmentioning
confidence: 99%
“…5,6 Earlier studies have documented prominent microglial activation and increased production of inflammatory cytokines and chemokines, including interferon gamma (IFN-g), interleukin (IL)-1b, IL-6, IL-12p40, tumor necrosis factor alpha (TNF-a), and chemokine (C-C motif) ligand 2 (CCL2) in the brain tissue and cerebrospinal fluid (CSF) of some individuals with ASD. 3,7 Although findings are not consistent, there is growing evidence indicating elevated plasma levels of pro-inflammatory cytokines, including TNF-a, IFN-g, IL-1b, IL-6, IL-12, IL-17A, IL-23, [8][9][10][11][12][13][14][15] and decreased plasma levels of the anti-inflammatory cytokines IL-10 and transforming growth factor-beta (TGF-b) in children with ASD as compared to controls. 1,16 Although the phenotypic and neurobiological heterogeneity in ASD might be underlying factors that account for inconsistent findings, it should also be noted that important confounding factors influencing immune markers, such as medication and body mass index (BMI), have not been adequately addressed in previous research.…”
Section: Introductionmentioning
confidence: 99%